An Examination of Grice’s Maxims in the Horror Novel Five Nights at Freddy’s by Scott Cawthon - Made Cahyana; Nur Ayomi (Universitas Islam Negeri Palopo, 2025)
Communication is a fundamental aspect of human interaction, and its effectiveness depends greatly on the cooperation between speakers. One influential framework for analysing this cooperation is Grice’s Cooperative Principle (1975), which consists of four conversational maxims: quantity, quality, relevance, and manner. This article aims to identify the types of cooperative maxims as proposed by Grice (1975) found in the horror novel Five Nights at Freddy’s: Fazbear Frights #2 Fetch by Scott Cawthon. The horror genre is particularly relevant for this analysis because it relies heavily in dialogue to build suspense, ambiguity, and psychological tension, making the application of conversational maxims especially significant. The objective of this study is to identify and classify the types of cooperative maxims, namely quantity, quality, relevance, and manner, that are used in the dialogues between characters. The research applies a descriptive qualitative method, with data collected through observation and note taking techniques, focusing on the dialogue between characters. The analysis revealed that the most frequently used type of maxim is the maxim of quantity (22 occurrences), followed by the maxim of quality (13), relevance (9), and manner (8). These findings indicate that the characters in the novel generally cooperate in communication by providing sufficient, truthful, relevant, and clear information. This research highlights how cooperative maxims are applied in fictional texts, contributing to effective communication and narrative coherence within the horror genre. In addition to narrative cohesion, the results of this study also suggest broader implications for literary and linguistic studies, demonstrating how pragmatic principles can serve as tools for understanding character dynamics, thematic construction, and stylistic strategies in fiction.